2008
DOI: 10.1002/mame.200800152
|View full text |Cite
|
Sign up to set email alerts
|

Rheological Features and Flow‐Induced Crystallization of Branched Poly[ethylene‐co‐(1,4‐cyclohexanedimethylene terephthalate)] Copolyesters

Abstract: A set of amorphous poly[ethylene‐co‐(1,4‐cyclohexanedimethylene terephthalate)] (PECT) copolymers containing 25 and 30% of 1,4‐cyclohexane dimethylene (CHDM) units and small amounts of branching agent pentaerythritol (PER) is investigated. The level of long chain branching was estimated by analyzing the positive deviation from $\eta _0 \sim\overline M _{\rm w}^{3.54}$ law. Branching also produced melt elasticity enhancement which is desirable for certain processing methods. Capillary extrusion experiments at 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 49 publications
(98 reference statements)
2
4
0
Order By: Relevance
“…In addition, the crystallization of LCB PP was more sensitive to shear flow than that of linear PP during the induction period even at low shear rates. Similar behaviour has been reported for other crystalline polymers with LCB structures, such as LCB polylactide and LCB polycarbonates [ 37 , 38 , 39 ].…”
Section: Introductionsupporting
confidence: 84%
“…In addition, the crystallization of LCB PP was more sensitive to shear flow than that of linear PP during the induction period even at low shear rates. Similar behaviour has been reported for other crystalline polymers with LCB structures, such as LCB polylactide and LCB polycarbonates [ 37 , 38 , 39 ].…”
Section: Introductionsupporting
confidence: 84%
“…Pure PET shows T g of 80.39°C and for IPA‐PEG copolymer series T g values are within 2°C difference up to 4% IPA‐PEG and above 4% IPA‐PEG T g starts decreasing rapidly. As reported elsewhere,15–30 the reduction of T g in PET is due to the kinking effect in the molecular structure, which arise due to the copolymer addition. The addition of comonomers in PET increases the T ch temperature and suggests that the crystallization takes place at higher temperature.…”
Section: Resultssupporting
confidence: 58%
“…Since this building block of CHDM is much larger (six additional carbon atoms) than the ethylene glycol unit it replaces, it does not fit in with the neighboring chains the way an ethylene glycol unit would. This interferes with crystallization and lowers the polymer's melting temperature 24–26. Replacement of MEG with PEG in PET polymer is also reported in the literature, and this copolymer is extensively used in biomaterial applications 27–29.…”
Section: Introductionmentioning
confidence: 97%
“…Crystallization depressed by branching was also reported in LCB PBS using trimethylol propane (TMP) as a BA . But Quintana and Santamaría et al . reported that LCB poly[ethylene‐co‐(1,4‐cyclohexanedimethylene terephthalate)] (PECT) branched by pentaerythritol (PER) showed improved flow‐induced crystallization because of favorable effect of branching to increase elongational rate at the entrance of the capillary.…”
Section: Introductionmentioning
confidence: 84%